Regionalizing the energy efficieny potential of the Swedish uilding stock: Case study for the KASK Region - Egestrand, Morten (My University, 2014)
This report describes a Master Thesis work at Chalmers University of Technology with the aim of assessing the energy savings potential in a part of the Swedish building stock. The work is a case study of the Västra Götaland (VG) and Halland regions, part of Western Sweden with Gothenburg as main city, and assesses residential as well as non-residential buildings. The assessment is done using the so called ECCABS model, which uses a bottom-up approach by modelling a building as one thermal zone and simulating the net energy demand for every hour of the year. The results are scaled up to represent the total building stock of the region. The input is based on a set of archetype buildings, described by their physical properties and technical installations, as well as climatic data. A baseline describing the current building stock is developed for the year 2010 by downscaling the datasets for the national building stock, for the residential and non-residential sectors individually. The residential sector is described with a representative sample of buildings (based on inventories), and the non-residential sector by archetype buildings (based on statistics). The simulation results are validated through the comparison with a Reference Energy System of the region, based on actual delivered energy to the building stock. The total energy demand for the region amounts to roughly 17.8 TWh/yr for the residential sector and 10.3 TWh/yr for the non-residential. A set of energy efficiency measures (ESMs) are applied separately to the residential and non-residential building stocks. The ESMs include improving the building envelope, upgrading the ventilation systems and other installations, as well as regulating the indoor temperatures. Three different “packages” of measures were also investigated, showing aggregated potentials for an overall improvement of the building envelope, decrease in power for lighting and appliances, as well as a maximum potential if all measures are implemented. A total potential of 12.7 TWh/yr of 52% in net energy savings is expected if all measures are applied. The largest saving potentials are found in upgrading the ventilations systems (including heat recovery) and improving the envelope by installing extra insulation. The results show that the political goals for the regions can be met, as the technical potential savings are larger than the current goals. From the simulation results, it is also clear that the current building regulations (BBR) do not provide a strong framework for reaching the efficiency goals of the region, and therefore other levels of benchmarking should be used instead. Due to a lack of detailed data related to the studied region, the results are related with large uncertainties, which indicates that the regionalisation of the assessment can be problematic. It is therefore necessary with more detailed data if a more in-depth analysis is needed.
Keywords: Energiteknik; Energy Engineering